2013
DOI: 10.1111/bij.12158
|View full text |Cite
|
Sign up to set email alerts
|

Variance in developmental event timing is greatest at low biological levels: implications for heterochrony

Abstract: Intraspecific variation in developmental event timing is common and may be the raw material from which heterochronies (altered timing of developmental events between ancestors and descendants) arise. However, our understanding of how variance in intraspecific developmental event timing is distributed across different hierarchical, biological levels is poor, despite recent evidence suggesting a genetic basis for such inter-individual differences. In the present study, we used high (temporal and spatial) resolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…An obvious candidate mechanism for heterochrony is for selection to act on intraspecific variation in the timing of developmental events (Spicer et al, 2011), and recent studies have shown that considerable standing variation in event timing exists (de Jong et al, 2009; Rundle et al, 2011; Tills et al, 2013b,c). Such variation may or may not have a genetic basis and could be enhanced through an interaction of the organism with its environment (Tills et al, 2011).…”
Section: Evolutionary Importance Of Variation In the Timing Of Devmentioning
confidence: 99%
See 1 more Smart Citation
“…An obvious candidate mechanism for heterochrony is for selection to act on intraspecific variation in the timing of developmental events (Spicer et al, 2011), and recent studies have shown that considerable standing variation in event timing exists (de Jong et al, 2009; Rundle et al, 2011; Tills et al, 2013b,c). Such variation may or may not have a genetic basis and could be enhanced through an interaction of the organism with its environment (Tills et al, 2011).…”
Section: Evolutionary Importance Of Variation In the Timing Of Devmentioning
confidence: 99%
“…This technology has recently been used in studies of event timing in gastropod ( R. balthica ) embryos from which it was possible to measure the timing of events such as the first heartbeat, mantle muscle flexing, crawling and shell and radula formation (Tills et al, 2013b). It revealed high levels of intraspecific variation (Tills et al, 2013c) that appeared to have a genetic basis (Tills et al, 2011). A parent–offspring comparison also revealed heritability in the timing of crawling within the egg capsule (Tills et al, 2013b) — current work is investigating whether such variation acts as the raw material for selection using a developmental plasticity approach.…”
Section: Evolutionary Importance Of Variation In the Timing Of Devmentioning
confidence: 99%
“…Furthermore, it is also possible that responses to predation threat during development are subtle or highly variable, and cannot be fully captured with the sequencing depth and pooling approach applied in this study. Variation in developmental traits including developmental plasticity has previously been reported for R. balthica (Rundle et al, 2011;Tills et al, 2013aTills et al, , 2013bTills et al, , 2010Tills, Spicer, & Rundle, 2010), and therefore, variation in the molecular response to predator kairomones is perhaps not surprising. Nonetheless, we acknowledge that this study has a low sample size (pools of 150 embryos, N = 3) and an associated limitation in statistical power and that this coupled with high levels of inter-sample variability may have contributed to a limitation in our ability to detect more subtle treatment-level responses.…”
Section: Analysis Of Differentially Expressed Transcripts Upon Predmentioning
confidence: 82%
“…When embryos reached the developmental stage E8 (approx. 115 hr after 4‐cell division, Tills, Rundle, & Spicer, ) or E9 (approx. 130 hr after 4‐cell division), three replicate samples from each of the four treatments (Ctrl—E8, Ctrl—E9, Pred—E8, and Pred—E9) were constructed from pooled individual embryos ( n = 150), fast‐frozen using liquid nitrogen, and subsequently stored at −80°C.…”
Section: Methodsmentioning
confidence: 99%
“…Embryonic development is a dynamic process with high levels of intraindividual temporal, spatial, and functional change, meaning that traditional approaches to its quantification at the whole-organism level can never be thorough. Furthermore, in addition to high levels of intraindividual change, embryonic development also exhibits high levels of interindividual variation [10], and therefore, an optimum approach to its study is to adopt longitudinal observation of large numbers of embryos [11]. This task is difficult to achieve and necessitates compromises in i) the number of embryos studied, ii) the number of phenomic measures quantified, iii) the precision with which measurements are made, and iv) the temporal resolution of measurements.…”
Section: Introductionmentioning
confidence: 99%